The Effect of Silica Fertilizer on the Yield and Shelf Life of Arugula (Eruca sativa) - Khal Mohammad Shaheen; Mahmoud Koushesh Saba; Behrooz Sarabi (Frontiers in Sustainable Science and Technology, 2025)
Nutrition is one of the factors affecting the quality and durability of products. Silica element is considered as one of the useful nutritional elements for plants. Therefore, in the present study, this element was used to feed before harvesting Arugula vegetable (Eruca sativa (Mill.) Thell.) and to investigate its effects after harvesting. The seeds were cultivated in June, 2021 in boxes (10 x 25 x 35) containing a mixture of perlite (50%) and cocopeat (50%) and in the research greenhouse of the Faculty of Agriculture, University of Kurdistan, so that 15 plants were grown in each box in 3 rows. The experiment was carried out as a completely randomized design before harvesting and factorial after harvesting with two factors and in three repetitions. The first factor was silica at three levels (0, 5 and 10 mM), the second factor was storage times in cold storage at four levels (harvest time, 4, 7 and 10 days after storage). Applying silica (potassium silicate) treatments in the amount of (0, 5 and 10 mM) was added to Hoagland's nutrient solution and after the establishment of plants (ten days after seed cultivation) on a daily basis until the end of the experiment. Weighing and drying traits of roots and shoots, total yield, leaf nitrate content before harvest and weight loss traits, total soluble carbohydrate, total phenol, flavonoid and vitamin C after harvesting Arugula. became The results showed that silica (10 mM) had a greater effect on the growth rate of roots, stems and leaves and their wet and dry weight in Arugula plant. The increase of silica decreased the accumulation of nitrate in the leaves. The effect of this fertilizer on the plant after harvest was investigated and it was observed that the treatment of 10 mM silica had a positive effect compared to the treatment of 5 mM silica and the control. Arugula treated with silica was kept at 4 degrees Celsius for 0, 4, 7 and 10 days and it was observed that soluble carbohydrates, chlorophyll content, weight, vitamin C and other measured factors which are marketable factors of the product in the application of this Fertilizers were well preserved during the storage period. In general, the use of silica fertilizers as pre-harvest nutrition can be used to increase the shelf life of Arugula after harvesting.